Respiratory mechanical and cardiorespiratory consequences of cycling with aerobars - Charlton, J. M.; Ramsook, A. H.; Mitchell, R. A.; Hunt, M. A.; Puyat, J. H.; Guenette, J. A. (Medicine & Science in Sports & Exercise, 2017)
Purpose Aerobars place a cyclist in a position where the trunk is flexed forward and the elbows are close to the midline of the body. This position is known to improve cycling aerodynamics and time trial race performance compared with upright cycling positions. However, the aggressive nature of this position may have important cardiorespiratory and metabolic consequences. The purpose of this investigation was to examine the respiratory mechanical, ventilatory, metabolic, and sensory consequences of cycling while using aerobars during laboratory-based cycling.